Comparison of Design Strategies for Promotion of β-Peptide 14-Helix Stability in Water - Vaz, Esther (2008)
Many short β-peptides adopt well-defined conformations in organic solvents, but specialized stabilizing elements are required for folding to occur in aqueous solution. Several different strategies have been developed to stabilize the 14-helical secondary structure in water, and here we provide a direct comparison of three such strategies. We have synthesized and characterized β-peptide heptamers in which either a salt bridge between side chains or a covalent link between side chains or a few cyclically constrained residues have been incorporated to promote 14-helicity. The incorporation of a salt bridge does not generate significant 14-helicity in water, according to CD and 2D NMR data. In contrast, incorporation of either a lactam bridge between side chains or cyclic residues results in stable 14-helices in water. The β-peptides featuring trans-2-aminocyclohexane-carboxylic acid (ACHC) residues show the highest 14-helical backbone stability, with hardly any sensitivity to pH or ionic strength. The β-peptides featuring a side chain-to-side chain cyclization show lower 14-helical backbone stability and higher sensitivity to pH and ionic strength, but an increased order between the side chains because of the cyclization.